Fish parasites (special issue) - Sayyaf Dezfuli, Bahram; Scholz, Tomáš (Parasitology, 2022)
Fish (Elasmobranchia and Actinopterygii) inhabit the majority of aquatic habitats globally. They are crucial for human nutrition but they may be negatively affected by parasitic protists and metazoan parasites. Fish parasites are also an extraordinary group of animals because of their ecological and evolutionary importance and unique adaptations to parasitism. They also play a key role in ecosystem functioning. In the present special issue, 13 review and research articles on major groups of fish parasites are provided to document the current advancement in our understanding of different aspects of their biology, ecology and associations with their fish hosts. The existing gaps in our knowledge of these peculiar animals are mapped and future trends in their research outlined.
Keywords: Animals; helminths; Mollusca; paraziti; biologická evoluce; molecular data; ecology; elasmobranchs; control; nemoci ryb; host–parasite relationships; lidé; Host-Parasite Interactions; Fish Diseases; Fishes; interakce hostitele a parazita; Aquaculture; ryby; parasitic crustaceans; Parasites; fish parasites; diversity; ekosystém; Ecosystem; ray-finned fish; zvířata; Biological Evolution; Myxozoa; Humans